The effect of PTU on Chemerin levels in hyperthyroid women during early pregnancy (Texas Journal of Agriculture and Biological Sciences, 2023)
This study aims to find out the effects associated with the use of propylthiouracil on Chemerin levels in pregnant women with hyperthyroidism. The current study was conducted on 60 women with hyperthyroidism and 60 women with normal thyroid glands, where they were divided into groups according to the time periods of pregnancy. Results: shows that there was significant increase in the levels of Chemerin in the groups of treatment with PTU compared with control groups and the increase positively correlated with the progression of pregnancy. Conclusion: PTU effect in Chemerin levels which increase with progression of pregnancy of hyperthyroid women.